Effects of Germination and Fermentation on Fatty Acid Profiles of Legume-Based Tempeh: A Systematic Review with Perspective on Cardiovascular Health - Salma Muti Hafizha; Siti Aisyah; Asep Kadarohman (Department of Chemistry, Faculty of Sciences and Informatics, University of Jenderal Achmad Yani, 2026)
Legume-based tempeh is a fermented food with the potential to support a healthy dietary pattern because it contains important nutritional components, including fatty acids. Germination and fermentation are known to influence lipid composition and fatty acid profiles in legumes, thereby potentially improving their nutritional value from a cardiovascular health perspective. This systematic review aimed to evaluate the effects of germination, fermentation, and their combination on the fatty acid profiles of legume-based tempeh. The PRISMA method was used to select and review 14 articles retrieved from the ScienceDirect and Scopus databases. The findings indicate that germination and fermentation can modify the fatty acid profile of tempeh, particularly through changes in saturated and unsaturated fatty acid contents. Several studies reported a decrease in saturated fatty acids and an increase in unsaturated fatty acids, including oleic acid, linoleic acid, and linolenic acid, although the magnitude of these changes varied depending on the type of legume, germination time, fermentation duration, microorganism, and analytical method used. Among the tempeh varieties reviewed, cowpea tempeh subjected to 24 h germination followed by 24 h fermentation showed a relatively favorable fatty acid profile, characterized by increased unsaturated fatty acids and an estimated linoleic acid to linolenic acid ratio of approximately 2.3:1.